1260Transvenous lead extraction: efficacy and safety of the procedure in octogenarian patients. (18th June 2020) - Giannotti Santoro, M; Segreti, L; Zucchelli, G; Barletta, V; Fiorentini, F; Di Cori, A; Della Tommasina, V; De Lucia, R; Bongiorni, M G
Abstract: Introduction: the management of patients with infection or malfunction of a cardiac implantable electronic device (CIED) may be challenging. Purpose: The aim of the study is to evaluate the safety and efficacy of transvenous lead extraction (TLE) in elderly patients. Methods: a retrospective analysis of patients who underwent to TLE in our center was performed. Patients were divided in two groups: 1) patients 80 years of age or older, 2) patients younger than 80 years. All patients were treated with manual traction or mechanical dilatation. Results: our analysis included 1316 patients, with a total of 2513 leads extracted. Group 1 (≥80 years) counted 202 patients and group 2 (<80 years) 1114 patients. The group of elderly patients presented more comorbidities, as hypertension, chronic kidney disease, atrial fibrillation and pulmonary disease. Patients 80 years of age or older had more pacemakers than ICDs, whereas the dwelling time of the oldest lead, the number of leads and the presence of abandoned leads was similar despite patients age. In group 1 the rate of radiological success for lead was higher than in group 2 (99.0% vs 95.9%; P < 0.001). The clinical success was obtained in 1273 patients (96.7%), without significative differences between groups (98.0% vs 96.4%; P = 0.36). Major complications occurred in 10 patients (0.7%), without significative differences (1.5% vs 0.6%; P = 0.24) (figure 1). Conclusion: TLE in elderly patients is a safe and effective procedure. In patients older than 80 years there are not more major complications than in younger patients, and the efficacy of the procedure seems to be superior.